Ectopic scrotum and penoscrotal transposition: Case report and literature review - Huang, Haoran; Liu, Xiangxia; Li, Zuoqing; Lin, Junjie; Yang, Hai; Xu, Zhe (Frontiers in Pediatrics, 2023)
Background: Ectopic scrotum is an extremely rare congenital scrotal malformation. Ectopic scrotum with VATER/VACTERL association is even rarer. There are no uniform guidelines for diagnosis and treatment. Clinical case: We described a two-year-five-month-old boy who has ectopic scrotum and penoscrotal transposition and reviewed relevant literature in this report. We performed laparoscopy exploration, rotation flap scrotoplasty, and orchiopexy and achieved a great result during the postoperative follow-up. Conclusions: Combined with the previous literature, we made a summary to come up with a plan for the diagnosis and treatment of ectopic scrotum. Rotation flap scrotoplasty and orchiopexy are worthy of considering operative methods in treating ES. For penoscrotal transposition or VATER/VACTERL association, we can treat the diseases individually.